An overview of mechanical properties and failure mechanism of FRP laminates with hole/cutout. Issue 20 (14th March 2023) - Gupta, Savita; Pal, Snehanshu; Ray, Bankim Chandra
Abstract: Aerospace and aircraft companies follow a pyramidal structure of testing, ranging from specimen tests to full‐scale structure tests, for aircraft structural design. At the base level, open hole strength evaluation is one of the qualification procedures for composite components. The holes are made in the structural components to accommodate bolts and rivets in order to assemble the parts into a single unit. Holes in the component are also used to fulfill functional requirements, such as the passage of wire bundles. FRP components are sensitive to these holes/cutouts as substantial decrement in the strength is observed in several experiments. The degradation in the strength of the component is due to stress concentration around the hole. This review aims to comprehend the effect of the hole on the mechanical properties of FRP laminates; the emphasis is mainly on CFRP laminates and experimental results. An overview of tensile, compressive, flexural and post buckling properties of laminates with the hole is presented to aid in the optimal design of the component. Finally, the failure mechanism during loading is discussed and described through a graphical presentation. Abstract :